Influence of rhizobacteria in production and nutraceutical quality of tomato fruits under greenhouse conditions - González Rodríguez, Gabriela; Espinosa Palomeque, Bernardo; Cano Ríos, Pedro; Leos Escobedo, Lucio; Sánchez Galván, Homero; Sáenz Mata, Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
An alternative in organic agriculture is the use of biofertilizers base rhizobacteria promoting plant growth and organic fertilizers “plant growth promoting rhizobacteria (PGPR) by its acronym in English”. The objective of the present work was to evaluate the effect of the inoculation of PGPR (Bacillus sp., Aeromonas sp. and Pseudomonas lini), using two substrates: S1= compost + river sand + perlite, and S2= river sand and as witnesses both substrates without PGPR (total of eight treatments), on the yield and quality of tomato fruits produced in the greenhouse. The experimental design used was completely randomized with three repetitions in a factorial arrangement (2 × 4), where factors A and B were: a) substrates and b) PGPR. The results indicate that the substrate S1 increased the contents of SST, lycopene, total sugars, ascorbic acid and the percentage of citric acid in tomato fruits. The inoculation of the strain Bacillus sp., Produced the highest contents of SST, lycopene and ascorbic acid in tomato fruits. Based on the set of responses in tomato fruits developed with different substrates and PGPR, the best treatment was T1 (Bacillus sp. + S1) which increased by 17.54, 8.77, 17.34, 31.31 and 11.52%, yield, contents of SST, lycopene, reducing sugars and ascorbic acid, respectively, in relation to the rest of the treatments. Therefore, the strain Bacillus sp. and the substrate base compost could be an alternative, because they improve the nutraceutical quality of fruits, without diminishing the yield of tomato in the greenhouse.
Keywords: Solanum lycopersicum L.; biofertilizers; compost; lycopene; PGPR